Morphological mutants of gibberella fujikuroi for enhanced production of gibberellic acid - Lale, Geetanjali; Jogdand, Vitthal V.; Gadre, Ramchandra V. (Journal of Applied Microbiology, 2006)
Aims: To examine the production of gibberellic acid by selected morphological mutants of Gibberella fujikuroi in liquid cultures. Methods and Results: Mutants of G. fujikuroi having different morphological characteristics were selected after UV irradiation. The production of gibberellic acid by mutants that had different hyphal lengths was examined in shake flasks in media with different concentrations of nutrients as well as different volumes of the medium. Fed-batch fermenter study was performed to evaluate the mutant Mor-25 for growth and production of gibberellic acid. The broth was analysed by high performance liquid chromatography for fusaric acid, the common mycotoxin produced by strains of Fusarium. A variety of morphological mutants having different mycelial and soluble pigmentation as well as colony morphologies were generated from G. fujikuroi upon exposure to UV radiation. A nonpigmented mutant (Car-1) was selected as intermediate parent and later, mutants Mor-1 and Mor-25 were selected based on their distinct morphology. The colonies on regeneration agar plates were small, compact and dry. In liquid medium, mutant Mor-25 grew in a micro-pelleted form and the mycelium had short, highly branched hyphae, curly at tips with thick, swollen cells. Mutant Mor-25 grew rapidly in a low-cost medium containing defatted groundnut flour, sucrose and salts. In media with higher nutrient concentrations as well as larger volumes, it produced twofold more gibberellic acid than the parent. Fusaric acid, the common mycotoxin, was absent in the fermentation broth of mutant Mor-25. The mutants have been deposited in National Collection of Industrial Microorganisms (NCIM), National Chemical Laboratory, Pune, India under following culture collection numbers (Car-1, NCIM 1323; Mor-1, NCIM 1322; and Mor-25, NCIM 1321). Conclusion: Growth of unpigmented, morphological mutants of G. fujikuroi that led to lower viscosity in fermentation broth resulted in increased production of gibberellic acid. Significance and Impact of Study: The use of morphological mutants that have lower viscosity in liquid cultures for gibberellic acid production is not reported earlier. Similar mutants can be useful for other types of fungal fermentations also.

Enhanced production of gibberellin A(4) (GA(4)) by a mutant of Gibberella fujikuroi in wheat gluten medium - Lale, Geetanjali; Gadre, Ramchandra V. (Journal of Industrial Microbiology & Biotechnology, 2010)
Mutants of Gibberella fujikuroi with different colony characteristics, morphology and pigmentation were generated by exposure to UV radiation. A mutant, Mor-189, was selected based on its short filament length, relatively high gibberellin A(4) (GA(4)) and gibberellin A(3) (GA(3)) production, as well as its lack of pigmentation. Production of GA(4) by Mor-189 was studied using different inorganic and organic nitrogen sources, carbon sources and by maintaining the pH of the fermentation medium using calcium carbonate. Analysis of GA(4) and GA(3) was done by reversed-phase high-performance liquid chromatography and LC-MS. The mutants of G. fujikuroi produced more GA(4) when the pH of the medium was maintained above 5. During shake flask studies, the mutant Mor-189 produced 210 mg l(-1) GA(4) in media containing wheat gluten as the nitrogen source and glucose as the carbon source. Fed-batch fermentation in a 14 l agitated fermenter was performed to evaluate the applicability of the mutant Mor-189 for the production of GA(4). In 7-day fed-batch fermentation, 600 mg l(-1) GA(4) were obtained in the culture filtrate. The concentration of GA(4) and GA(3) combined was 713 mg l(-1), of which GA(4) accounted for 84% of the total gibberellin. These values are substantially higher than those published previously. The present study indicated that, along with maintenance of pH and controlled glucose feeding, the use of wheat gluten as the sole nitrogen source considerably enhances GA(4) production by the mutant Mor-189.
Keywords: Fermentation; GA(4); Gibberella fujikuroi; Mutant; Wheat gluten

Production of bikaverin by a Fusarium fujikuroi mutant in submerged cultures - Lale, Geetanjali; Gadre, R. V. (AMB Express, 2016)
A variety of mutants having different colony characteristics, morphology and soluble pigmentation were generated from Fusarium fujikuroi by exposure to UV radiation. Mutants were selected that formed dry, compact, small colonies with reddish-violet pigment on regeneration agar plates. The production of bikaverin by Mut-4 was examined in shake flasks in media with different nitrogen and carbon sources. The optimal C: N ratio for the maximal bikaverin production by Mut-4 was 150: 1. It produced still higher bikaverin (6.3 g l(-1)) in a medium containing defatted cottonseed meal as nitrogen source, in combination with glucose. Bikaverin produced was extracted, purified and characterized by UV-visible and NMR spectroscopy. Bikaverin production in the present investigation was substantially higher than that reported by earlier investigators in submerged and solid-state fermentations.
Keywords: Bikaverin; Fusarium fujikuroi; Gibberella fujikuroi; Pigment production; Submerged cultures